DIGITAL MANAJEMEN ASUPAN CAIRAN PASIEN HEMODIALISIS : LITERATUE REVIEW - Zaky Mubarak (LPPM STIKES Muhammadiyah Kendal, 2021)
Digital recording is a method that has the potential to help chronic disease (CKD) patients undergoing hemodialysis manage problems related to fluid intake. This literature review examines the mobile application intervention for hemodialysis patients, application characteristics, application, effectiveness in changing user behavior, and user satisfaction. The method used is a literature review using articles sourced from electronically based data such as EBSCO, Google Scholar, Pubmed and Scopus with the keywords diet management, fluid status, hemodialysis in the period 2010-2021. The results are five studies describing the evaluation of changes in dietary behavior related to with self-management has a positive change impact. Conclusion: According to the current study, digital recording using an application can hold promise in hemodialysis patients' self-management of fluid intake dietary behavior.